The dark history of America's old West - Callery, Sean. (New York : Marshall Cavendish Benchmark, 2010)
"A collection of dark deeds from America's old West"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Pioneers -- West (U.S.) -- History -- 19th century -- Juvenile literature; Indians of North America -- Wars -- 1866-1895 -- Juvenile literature; Indians, Treatment of -- North America -- Juvenile literature; Outlaws -- West (U.S.) -- History -- 19th century -- Juvenile literature; West (U.S.) -- History -- 19th century -- Juvenile literature